Binding and functional structure-activity similarities of 4-substituted 2,5-dimethoxyphenyl isopropylamine analogues at 5-HT2A and 5-HT2B serotonin receptors - Hemanth, Prithvi; Nistala, Pallavi; Nguyen, Vy T.; Eltit, Jose M.; Glennon, Richard A.; Dukat, Małgorzata (Frontiers in Pharmacology, 2023)
Certain 4-substituted analogs of 1-(2,5-dimethoxyphenyl)isopropylamine (2,5-DMA) are psychoactive classical hallucinogens or serotonergic psychedelic agents that function as human 5-HT2A (h5-HT2A) serotonin receptor agonists. Activation of a related receptor population, h5-HT2B receptors, has been demonstrated to result in adverse effects including cardiac valvulopathy. We previously published on the binding of a several such agents at the two receptor subtypes. For a series of 13 compounds, it is demonstrated here that i) their rat 5-HT2 receptor affinities are significantly correlated with their h5-HT2A (r = 0.942) and h5-HT2B (r = 0.916) affinities, ii) as with r5-HT2 receptor affinity, h5-HT2A affinity is correlated with the lipophilicity of the 4-position substituent (r = 0.798), iii) that eight of the ten compounds examined in functional (Ca+2 mobilization) assays acted as h5-HT2B agonists (4-substituent = H, F, Br, I, OCH2CH3, NO2, nC3H7, tC4H9) and two (n-hexyl and benzyl) as antagonists, iv) h5-HT2B affinity but not action was correlated with the lipophilicity of the 4-position substituent (r = 0.750; n = 10). The findings suggest that h5-HT2B receptor affinity, and its relationship to substituent lipophilicity, might be approximated by rat and h5-HT2A affinity but cannot be used as a predictor of h5-HT2B agonist action of 2,5-DMA analogs. Furthermore, given that certain 2,5-DMA analogs are on the clandestine market, their potential to produce cardiac side effects via activation of h5-HT2B receptors should be considered.